The value of genetic and genomic technologies : workshop summary / Theresa Wizemann and Adam C. Berger, rapporteurs ; Roundtable on Translating Genomic-Based Research for Health ; Board on Health Sciences Policy ; Institute of Medicine of the National Academies. - Wizemann, Theresa M.; Berger, Adam C. (National Academies Press, 2010)
"Knowing one's genetic disposition to a variety of diseases, including common chronic diseases, can benefit both the individual and society at large. The IOM's Roundtable on Translating Genomic-Based Research for Health held a workshop on March 22, 2010, to bring together diverse perspectives on the value of genetic testing, and to discuss its use in clinical practice."--Home page.